Comparative Evaluation of Curcumin Gel With Diode Laser (970 nm) Versus Diode Laser Alone For Pocket Depth Reduction in Chronic Localised Periodontitis – A Split-Mouth Randomized Clinical Trial: Curcumin gel vs. diode laser for pocket depth reduction in periodontitis - Sharath, Sanidhya; Kamath, Deepa G; Shenoy, Nina (Journal of Lasers in Medical Sciences, 2025)
Introduction: The fusion of curcumin gel and laser technology offers a promising solution for periodontal pocket reduction. Harnessing the anti-inflammatory prowess of curcumin and the precision of laser, this approach enhances periodontal therapy efficacy, fostering improved oral health outcomes. Methods: This split-mouth study was conducted on nine patients. After scaling and root planing (SRP), curcumin gel with a diode laser and a diode laser alone were used in the test and control groups, respectively. The plaque index (PI), modified sulcus bleeding index (SBI), probing pocket depth (PPD), and clinical attachment loss (CAL) were recorded at baseline and three months. Results: The results revealed that both the diode laser and curcumin gel reduced periodontal pocket depths, but a greater reduction was observed in the test group than in the control group. Conclusion: It can be concluded that both control and experimental gel can be used as an adjunct to SRP, but curcumin gel was more effective when used with Diode laser therapy (970nm) in the treatment of periodontal pockets with a significant reduction in the scores of the indices when compared to the baseline values.